1985
DOI: 10.1159/000180050
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Pituitary Responses to Physical Exercise in Athletes and Sedentary Subjects

Abstract: Serum growth hormone (GH), prolactin (PRL), cortisol, luteinizing hormone (LH), follicle-stimulating hormone (FSH) and thyroid-stimulating hormone (TSH) levels were evaluated before and after a bicycle ergometer exercise test in 8 male competitive volleyball players and in 8 sedentary healthy males of the same age. Increased serum GH and cortisol values after exercise in both groups were found, whereas an exercise-induced PRL release was observed in athletes only. Serum levels of LH, FSH and TSH were unaffecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0
5

Year Published

1987
1987
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 17 publications
1
6
0
5
Order By: Relevance
“…It was suggested that thyroid hormones may have a fundamental active role in the adaptation of the body to stress, including physical exertion (Rone et al, 1992). Reports on the effects of exercise for thyroid hormone and TSH are inconsistent; some show an increase but others indicate that there is a tendency towards decrease (Kirkeby et al, 1977;Galbo et al, 1977;Rolandi et al, 1985;Dessypris et al, 1980, O'Connel et al, 1979 The present studies show that plasma total TSH, T 3 , T 4 , calcitonin, and PTH levels increased during CDSB Qi-training in the elderly. But TSH has been reported to decline during individual practice sessions of the transcendental meditation (Jervning etal, 1987).…”
Section: Discussionmentioning
confidence: 39%
See 1 more Smart Citation
“…It was suggested that thyroid hormones may have a fundamental active role in the adaptation of the body to stress, including physical exertion (Rone et al, 1992). Reports on the effects of exercise for thyroid hormone and TSH are inconsistent; some show an increase but others indicate that there is a tendency towards decrease (Kirkeby et al, 1977;Galbo et al, 1977;Rolandi et al, 1985;Dessypris et al, 1980, O'Connel et al, 1979 The present studies show that plasma total TSH, T 3 , T 4 , calcitonin, and PTH levels increased during CDSB Qi-training in the elderly. But TSH has been reported to decline during individual practice sessions of the transcendental meditation (Jervning etal, 1987).…”
Section: Discussionmentioning
confidence: 39%
“…However, recent data on the thyroid hormone profile of subjects in prolonged moderate exercise agree with the results of our experiment. Thyroid stimulating hormone (TSH) secretion has been reported after stress test (Sowers et al, 1977) and acute challenges such as strenuous exercise (Rolandi et al 1985). We found no correlations between TSH and T 3 , T 4 during the experiments, indicating an uncoupling between pituitary stimulation and thyroidal secretion.…”
Section: Discussionmentioning
confidence: 51%
“…However, their subjects were professional athlethes, whereas our subjects were well-trained non-athletes and this might explain the differ¬ ence. Further support for a difference in the PRL response during exercise in athletes and nonathletes was recently presented by Rolandi et al (1985) who found that PRL increased after exer¬ cise in athletes, but not in sedentary subjects. Conflicting results were reported by Grossman et al (1984) who demonstrated an enhanced PRL response to exercise after 12 mg of naloxone.…”
Section: Discussionmentioning
confidence: 84%
“…Overall, training can lead to different effects, and the magnitude of the hGH release can be different according to the nature of the training itself (eg, for the same duration and total work effort, hGH levels are higher after a high‐intensity anaerobic work compared with low‐intensity anaerobic work), and to individual features such as age, sex, body composition, initial training, and fitness level . When elite athletes are compared with nonelite athletes and sedentary people, hGH levels are significantly higher, although no clear consensus is available concerning IGF‐1, which probably reflects the inter‐individual variability of this hormone . Age‐dependent levels of hGH‐related markers are predictable in elite athletes, and they are independent of sporting category, suggesting that well‐trained people have their own serum and urinary ranges for both hGH and IGF‐1 …”
Section: Introductionmentioning
confidence: 99%
“…10 When elite athletes are compared with nonelite athletes and sedentary people, hGH levels are significantly higher, although no clear consensus is available concerning IGF-1, which probably reflects the inter-individual variability of this hormone. 11,12 Age-dependent levels of hGH-related markers are predictable in elite athletes, and they are independent of sporting category, 13 suggesting that well-trained people have their own serum and urinary ranges for both hGH and IGF-1. 14 Similarly, the role of cortisol (C) in the maintenance of body homeostasis in response to stressors, acute physical exercise, and chronic training is widely demonstrated both in athletes and sedentary people.…”
mentioning
confidence: 99%